Literasi Digital Sitasi Dan Referensi: Pelatihan Mendeley Pada Mahasiswa Fisip Universitas Halu Oleo - Sarinah Sarinah; La Ode Agus Said; Muh. Rijal; Rasmin Rasmin; Nur Azizah Rasudu (P3M Politeknik Negeri Malang, 2025)
Digital literacy training on citations and references using the Mendeley application was conducted as an effort to improve the ability of students at the Faculty of Social and Political Sciences, Halu Oleo University, to manage references academically and ethically. The main objective of this activity was to equip students with technical skills in using Mendeley to facilitate the process of scientific writing, avoid plagiarism, and enhance academic awareness in citing library sources. The implementation method involved four main stages: program planning, socialization and technical preparation, conducting interactive training, and evaluation and follow-up. The training was conducted in a hybrid format with a participatory approach, including lectures, live demonstrations, practical use of Mendeley, and question-and-answer sessions to deepen participants' understanding. The training results showed a significant improvement in students' ability to operate Mendeley, manage references, and automatically insert citations into scientific writing documents. Based on the evaluation questionnaire, 88% of participants stated that the training was very beneficial, 82% were new Mendeley users but were able to install and operate it independently, and 91% recommended that this training be conducted on a regular basis. Overall, the Mendeley training proved effective in enhancing students' digital literacy competencies and supporting the improvement of scientific writing quality among students at the Faculty of Social and Political Sciences, Halu Oleo University.